Bud load management on table grape yield and quality – cv. Sugrathirteen (Midnight Beauty®) - Feitosa,Carlos Augusto Menezes (2018)
ABSTRACT Viticulture is an activity of great economic and social importance in the Submedium region of the São Francisco River Valley, with emphasis on table grape and wine production. With the increasing expansion of the viticulture, a growing number of alternatives that do not affect fruit quality have been studied to maximize table grape yield, such as pruning and load adjustment. The aim of the present study was to evaluate the influence of different bud loads on canopy management to enable the marketable and economic production of cv. Sugrathirteen (Midnight Beauty®) in the submedium region ofthe São Francisco River Valley. This study was carried out for two years (2014/2015) in an experimental area for the introduction of new cultivars patented by Prodomo Farm in the municipality of Petrolina, Pernambuco, Brazil. The experiment was conducted in a randomized block factorial 2 × 5 design, with two seasons and 5 treatments, 6, 8, 10, 12 and 14 buds short_textwhich correspond toshort_text 17, 23, 29, 34 and 40 buds·m–2 short_textrespectivelyshort_text, distributed in 4 plots, considering five plants per replicate. Our results show that pruning seasons significantly affected sprouting percentage. However, the difference in bud load influenced this variable, with higher values in the pruning at 14 buds in both seasons. According to the results, the selection of pruning system according to bud load and to genetic features of the cultivar, and their interaction with the environment, produced higher yields in pruning with 10 buds, without negatively affecting grape quality.